2013
DOI: 10.1001/jamasurg.2013.3738
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Screening Mammography in the Veterans Health Administration

Abstract: Our institution has rapidly and successfully expanded screening mammography. Higher mammography volumes have been associated with increased use of non-VA breast care services and increased time to definitive treatment. Appropriate counseling regarding BCT was consistently documented, and mastectomy in BCT-eligible patients was largely the result of patient preference or clinical/social factors. Our data suggest that as patient volumes increase with intensified screening, VA hospitals may benefit from acquiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…More aggressive breast cancer screening recommendations and increased mammogram sensitivity have resulted in a greater incidence of nonpalpable breast lesions. 1,2,16 More advanced and precise biopsy techniques with radiographic or ultrasound guidance have also increased the need for excision of nonpalpable breast lesions. 2 WLE is currently the most common method used for excising nonpalpable breast lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More aggressive breast cancer screening recommendations and increased mammogram sensitivity have resulted in a greater incidence of nonpalpable breast lesions. 1,2,16 More advanced and precise biopsy techniques with radiographic or ultrasound guidance have also increased the need for excision of nonpalpable breast lesions. 2 WLE is currently the most common method used for excising nonpalpable breast lesions.…”
Section: Discussionmentioning
confidence: 99%
“…T HE INCREASE IN screening mammography and diagnostic breast imaging has resulted in increasing numbers of biopsies of suspicious breast lesions. 1,2 In the era before aggressive screening mammography, breast lesions commonly presented as palpable areas of concern. Current screening mammography has allowed for the detection of breast abnormalities at an earlier nonpalpable stage.…”
mentioning
confidence: 99%
“…48,[89][90][91] Innovations and practice redesigns, including using women's health PCPs and care coordinators, enterprise-wide educational programs and resources, gender-specific clinical decision support and performance management tools, and telehealth pro-grams, have transformed VA's care for women Veterans. 30,40,[46][47][48][49]92,93 VA can build on this foundation to foster further innovation and research on optimizing coordination of care for reproductive health malignancies which, in turn, would provide insights that VA may be able to apply more broadly in caring for women Veterans.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some VA sites have begun utilizing non-provider staff members in the role of care coordinators for cervical and breast cancer screening. 49 These individuals are generally responsible for ensuring that results are obtained, communicated to the patient, and, when needed, additional follow-up actions are taken. VA's implementation of this approach has high-promise, as data from other settings have shown that organizational interventions using non-provider staff for prevention tasks, such as screening, are particularly effective• 41 Research is needed to examine the effectiveness of and implementation factors associated with VA's use of dedicated reproductive health cancer coordinators.…”
Section: Prevention and Screeningmentioning
confidence: 99%
See 1 more Smart Citation